A novel paradigm CNG dual-fuel strategy to reduce engine emission of a CRDI engine: a green fuel and multi-objective optimization approach / Jibitesh Kumar Panda ... [et al.] - Panda, Jibitesh Kumar; Peng, Jun; Deb, Payel; K., Rajesh; Vadlamudi, Srikanth; Dewangan, Niraj Kumar; Pachauri, Nikhil; Kumari, Shweta (UiTM Press, 2025)
This study aimed to reduce emissions—specifically smoke, carbon monoxide, nitrogen oxides, and unburnt hydrocarbon alongside brake specific fuel consumption (BSFC) in a dual-fuel mode using Mahua oil blended with compressed natural gas, methanol, and ethanol. BSFC, a key measure of engine fuel efficiency, and the emissions were evaluated with load, injection timing, injection duration, and fuel strategy as input parameters. To minimize trials, Taguchi's L9 orthogonal array was used, with Grey Relational Analysis optimizing the process. The study identified load as the most influential factor. Results showed significant reductions in smoke, CO, NOx, and UHC emissions, while BSFC improved measurably. The study concluded that using this optimization approach effectively enhances engine performance and reduces environmental impact in dual-fuel systems.